Fat Content and Antioxidant Activity in Coconut Milk-Based Ice Cream with Cashew Milk Combination - Pangastuti, Diana; Kurnia, Pramudya (Newinera Publisher, 2024)
Among frozen dairy products, ice cream is a product that is produced and consumed in large quantities. Coconut milk contains different types of fats, such as saturated fats, polyunsaturated fats, omega-3 fats, omega-6 fats, and monounsaturated fats. To improve the quality of ice cream in terms of taste, aroma, texture, and flavor, one can combine two ingredients, namely coconut milk and cashew milk. Cashews contain 40-57% fat and 21% protein. The purpose of this study is to measure fat content and antioxidant activity and determine the effect of cashew milk combination on fat content and antioxidant activity of coconut milk-based ice cream. This study is an experimental study with a factorial design in the form of a Completely Randomized Design (CRD). It consists of three treatments with different percentage compositions of coconut milk and cashew milk: A (60%:40%), B (50%:50%), and C (40%:60%). The experiment was conducted with two replications The parameters analyzed were fat content and antioxidant activity. The data obtained were processed using editing, coding, tabulating, and entry procedures. Furthermore, the data were analyzed using statistical tests in the form of One-Way ANOVA and the Kruskal-Wallis test to determine the effect of the combination of coconut milk and cashew milk on ice cream products. The results showed that there was a significant difference in the use of coconut milk and cashew milk on fat content with p = 0.000 (p ≤ 0.05) and antioxidant activity with p = 0.001 (p ≤ 0.05).